Movement and the Watery Imaginary in the Contemporary North American Feminist Poetic - Tess Marie Patalano (Humanities)
What can hybridity teach us? The answer I posit is–like water–to embrace movement in all its forms. We are currently experiencing the sixth mass extinction event on earth and yet few scholars give prolonged attention to how we are to sustainably move our human inheritances forward on this increasingly uninhabitable planet. Reflecting on the work of transnational poets, specifically South Korean poet Kim Hyesoon translated through Korean American poet Don Mee Choi and Lebanese American poet Etel Adnan, we are reminded of the myriad ways in which humans can move and survive in a foreign yet familiar world. This paper finds its support in the confluence of transnational contemporary feminist poetics, formalism, environmentalism, and posthumanism. Through the use of various critical discourses, this paper considers how movement and its hybrid capacities offer a new understanding of contemporary North American poetics. In this sense, a poem should be viewed as a dynamic temporal cybernetic system, a vessel, full of energy, simultaneously pulsing with the changing movements and constrictions of everyday life.